Prevalence and correlates of screen time, eating behavior and co-occurring of screen-time and unhealthy eating behavior among young Children in Pokhara Metropolitan. - Sharma, Bimala (2020)
ABSTRACT: Objective: The study aimed to find out the status and correlates of screen time, eating behavior and co-occurring of screen-time and unhealthy eating behavior among young children aged 5 to 9 years in Pokhara metropolitan city. Methods: A cross-sectional study was conducted among school going children aged 5 to 9 years in Pokhara metropolitan. Three hundred and sixty face to face interviews were done with one of the parents of the selected children with the help of semi-structured questionnaire. In addition, six in-depth interviews were also conducted with parents. Data collection was done from March 8 to September 4, 2020. Children were classified into high screen time groups based on guidelines of >2 hours screen viewing each day as a standard. The fruit consumption was dichotomized to define low fruit consumption as 5-6 days per week or less; the vegetable consumption was grouped to define low vegetable consumption as <2 servings a day, and low fruit and vegetables consumption was dichotomized to define low fruit and vegetables as < 3 servings a day as most of the children did not meet the recommended serving of fruit, vegetables, and fruits and vegetables. At least one serving a day was categorized as high consumption of energy dense food. Descriptive, bivariate and multivariate analyses were computed for quantitative data. All inferential analyses were conducted at 5% level of significance. Chi square test and independent sample t test were applied to show association of each independent variable with outcome variables. Multivariate binary logistic regression test was applied to find out the correlates of dependent variables. Qualitative data was analyzed using the thematic analysis technique. Ethical approval was taken from Nepal Health Research Council. Results: Out of total 360 children, 54.7% were males; 35.6% were at age of 9 years and 31.4% were of grade one. Total screen time >2 hours per day was 48.6%; including 37% in public school and 54.9% in private school children. Male children were more likely to have >2 hours screen time each day as compared to female children. Access to media devices or gadgets at home was significantly associated with screen time of >2 hours among children. Parental offering of screen time to keep children inside the home, to feed them and to make free time for themselves, and parental screen time were significantly associated with screen time >2 hours among children aged 5 to 9 years in multivariate analysis. However, socio-demographic factors like ethnicity, type of school, type of family, average income of the family, parental education and parental occupation were not associated with screen time among subjects with high screen time. The study found poor eating practices among children aged 5 to 9 years; most of children did not meet the recommended serving standard of fruits, vegetables, and fruit and vegetables consumption. The mean fruits, vegetables, and fruits and vegetables servings were found 0.47, 1.18 and 1.65, respectively. In the study, only one child met the recommendation for vegetable consumption; 3.4% met the recommendation for fruits and none of child met the recommendation of fruit and vegetables consumption each day. Of total, 79.4% consumed fruit less than once a day; 53.6% consumed vegetables less than twice a day; 87.2% consumed fruits and vegetables less than three times a day. The study found that age, sex, types of family were not statistically significant with fruits and vegetable consumption; ethnicity, education and average income of the family were significant in bivariate analysis only. The children from private schools were more likely to consume fruits and vegetables as compared to children from public school. We found that 48.3% of children consumed energy dense food at least once a day. There was significant association of children's age, gender, parent's education, parents' occupation and type of school with energy dense food consumption in bivariate analysis. Family type, ethnicity and average family income were not statistically significant with energy dense food consumption. Buying snacks at shop for school lunch increased the likelihood of children's consumption of energy dense food by more than two fold as compared to those children who take home made food. The current study revealed that 36.4% had no or one risk behavior, 39.1% had two risk behaviors and 24.4% had three risk behaviors. The study revealed that having cable at home, having personal gadget of child, number of TV at home, offering gadgets to make children eat, offering gadgets to have free time and offering gadget to keep children inside were significantly associated with presence of multiple risk behaviors. None of the socio-demographic variables showed significant variation of presence or absence of multiple risk behaviors among children. Conclusion: There is a high prevalence of screen time and poor eating habit, and clustering of risk behaviors among children aged 5 to 9 years. Interventions should focus to address reduction in screen time and improve eating habit patterns, including device availability and accessibility for the children. Therefore, it requires a combination of efforts from individual, family, school and society Key Words: Screen time. Fruit and vegetables consumption, Energy dense food consumption, Co-occurring of unhealthy behaviors, Children